2006
DOI: 10.2136/vzj2005.0088
|View full text |Cite
|
Sign up to set email alerts
|

Resolving Structural Influences on Water‐Retention Properties of Alluvial Deposits

Abstract: With the goal of improving property‐transfer model (PTM) predictions of unsaturated hydraulic properties, we investigated the influence of sedimentary structure, defined as particle arrangement during deposition, on laboratory‐measured water retention (water content vs. potential [θ(ψ)]) of 10 undisturbed core samples from alluvial deposits in the western Mojave Desert, California. The samples were classified as having fluvial or debris‐flow structure based on observed stratification and measured spread of par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…[1]), thus increasing computational efficiency. For example, effective porosity n e was fixed at 75% of the maximum observed water content for each hydrogeologic unit, equivalent to assuming that, under conditions of field saturation, 25% of the pore space is occupied by trapped air, as is consistent with empirical trends for desert deposits similar to those considered in this study (Winfield et al, 2006). These fixed porosity values additionally agree with gravimetric measurements on core samples from the active wash deposits and the Holocene soil (no core was taken from the Pleistocene soil).…”
Section: Methodsmentioning
confidence: 77%
“…[1]), thus increasing computational efficiency. For example, effective porosity n e was fixed at 75% of the maximum observed water content for each hydrogeologic unit, equivalent to assuming that, under conditions of field saturation, 25% of the pore space is occupied by trapped air, as is consistent with empirical trends for desert deposits similar to those considered in this study (Winfield et al, 2006). These fixed porosity values additionally agree with gravimetric measurements on core samples from the active wash deposits and the Holocene soil (no core was taken from the Pleistocene soil).…”
Section: Methodsmentioning
confidence: 77%
“…Structure was defined as the arrangement of soils resulting from aggregate formation, depositional sorting, shrink‐swell processes, and macropores from animal burrows and root channels. Texture was determined to have a greater influence than structure on the water retention properties of the water‐laid and debris‐laid sediments [ Winfield et al , 2006].…”
Section: Conceptual Model Of Alluvial Fansmentioning
confidence: 99%
“…Specifically, we considered how the shape of the fan and the sequence of fan surfaces influence where infiltration occurs using a two dimensional (2‐D) distributed numerical model of synthetic fans with coupled surface flow and infiltration. Another characteristic of fan morphology with significance for infiltration is the permeability of fan sediments, which is related to the depositional environment, fan age, soil development, and geology of the source basin [ Weissmann et al , 2002a; Young et al , 2004; Winfield et al , 2006]. Using the numerical model, we also examined how fan morphology, including sediment permeability, influences the partitioning of flow between on‐fan flows and those that extend downslope of the fan environment.…”
Section: Introductionmentioning
confidence: 99%
“…Winfield et al . () investigated the structural influence on the water retention properties of alluvial deposit to improve the property‐transfer model predictions of unsaturated hydraulic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Walczak et al (2006) suggested the prediction of WRC using three soil physical parameters. Winfield et al (2006) investigated the structural influence on the water retention properties of alluvial deposit to improve the property-transfer model predictions of unsaturated hydraulic properties.…”
Section: Introductionmentioning
confidence: 99%